Problem-Based Learning Model Assisted by GeoGebra for Students' Mathematical Conceptual Understanding - Jazuli, La Ode Ahmad; Kodirun; Zahra, Fiqra Purnama (Jurnal Amal Pendidikan, 2024)
This study is motivated by the challenges many students face in understanding abstract concepts in mathematics, which negatively impacts their learning outcomes and critical thinking skills, making it difficult for them to follow lessons effectively. The instructional models commonly used are often ineffective in fostering a deep understanding of concepts among students. Therefore, the application of the Problem Based Learning (PBL) model, supported by GeoGebra, is considered capable of enhancing students’ conceptual understanding through interactive visualization. This study aims to examine the influence of the Problem Based Learning (PBL) model assisted by GeoGebra on the ability to understand mathematical concepts of grade X students of SMA Negeri 1 Tongauna. This type of research is a quasi-experiment with a Posttest-Only Control Design research design. The population of this study is all students of class X of SMA Negeri 1 Tongauna. With two sample classes selected, namely class X.3 and class X.4. Sample selection uses a simple random class technique. The data of the research results were collected through observation sheets and tests of students' ability to understand mathematical concepts. The data analysis techniques in this study are descriptive and inferential analysis. Based on the results of the descriptive analysis, it is known that the values and classifications in the experimental class are superior to the control class. The results of the inferential analysis obtained the values of   and  with  Because , then  is rejected, leading to the conclusion that this study demonstrates a significant effect of the GeoGebra-supported PBL model on the mathematical conceptual understanding ability of tenth-grade students at SMA Negeri 1 Tongauna.